2016
DOI: 10.1021/acs.organomet.6b00566
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Calcium Hydride Complexes by Fine Tuning of Amidinate Ligands

Abstract: A range of symmetric amidinate ligands RAmAr (R is backbone substituent, Ar is N substituent) have been investigated for their ability to stabilize calcium hydride complexes of the type RAmArCaH. It was found that the precursors of the type RAmArCaN­(SiMe3)2 are only stable toward ligand exchange for Ar = DIPP (2,6-diisopropylphenyl). The size of the backbone substituent R determines aggregation and solvation. The following complexes could be obtained: [RAmDIPPCaN­(SiMe3)2]2 (R = Me, p-Tol), RAmDIPPCaN­(SiMe3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
75
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 62 publications
7
75
0
10
Order By: Relevance
“…The calcium hydride pathway A was further confirmed by stoichiometric reactions with a recently introduced well-defined calcium hydride complex 16 (3, Fig. 6).…”
Section: Nature Catalysismentioning
confidence: 61%
See 2 more Smart Citations
“…The calcium hydride pathway A was further confirmed by stoichiometric reactions with a recently introduced well-defined calcium hydride complex 16 (3, Fig. 6).…”
Section: Nature Catalysismentioning
confidence: 61%
“…The synthesis and structure of complex 3 ( Fig. 6) have been reported previously 16 . Stoichiometric conversions of 3 with imine and subsequently with H 2 (6 bar) were performed in a high-pressure NMR tube and were monitored by 1 H NMR (see Supplementary Methods).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Thespectator ligand Ls hould be bulky,m ultidentate and strongly bound to Scheme 1. [13] While lessons learned now allow for access to ag rowing number of calcium hydride complexes,the heavier and much more challenging strontium and barium hydride complexes have hitherto remained elusive.I ncreasing the size of the metal does not only result in faster ligand exchange [14] but also makes it increasingly difficult to prevent Schlenk equilibria by steric hindrance.Additionally,the inherently higher reactivity of heavier Group 2m etal complexes poses problematic decomposition pathways.O ur attempts to control ligand exchange by use of extraordinarily large ligands has so far failed. prevent formation of homoleptic species through the Schlenk equilibrium:2LAeH Q L 2 Ae + AeH 2 fl.…”
mentioning
confidence: 99%
“…The simulations also supported the proposed stepwise mechanism for the catalytic cycle. Finally, Bauer et al used a previously reported calcium hydride complex 11 as a model of the proposed catalytic hydride intermediate, and found that it reacts with an aldimine and hydrogen gas in a way that is consistent with the proposed catalytic cycle.…”
Section: O U G L a S W St E P H A Nmentioning
confidence: 90%